2018
DOI: 10.1556/2006.7.2018.22
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity traits and addiction-related behaviors in youth

Abstract: Background and aimsImpulsivity is a risk factor for addictive behaviors. The UPPS-P impulsivity model has been associated with substance addiction and gambling disorder, but its role in other non-substance addiction-related behaviors is less understood. We sought to examine associations between UPPS-P impulsivity traits and indicators of multiple substance and non-substance addiction-related behaviors in youth with varying involvement in these behaviors.MethodsParticipants (N = 109, aged 16–26 years, 69% males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 91 publications
(127 reference statements)
8
87
0
8
Order By: Relevance
“…The contribution of personality factors to ratings of CSB symptoms was examined in 10 studies. 77,[103][104][105][106][107][108][109][110] In a study of Shimoni and colleagues, 103 81 women and 186 men were recruited via internet sites used for finding sexual partners. Results of this investigation showed that women (as compared to men) obtained lower scores on Sexual Addiction Screening Test (SAST), 111 they were less open to experiences and more neurotic (as assessed by the Big Five Index).…”
Section: Personality Traitsmentioning
confidence: 99%
“…The contribution of personality factors to ratings of CSB symptoms was examined in 10 studies. 77,[103][104][105][106][107][108][109][110] In a study of Shimoni and colleagues, 103 81 women and 186 men were recruited via internet sites used for finding sexual partners. Results of this investigation showed that women (as compared to men) obtained lower scores on Sexual Addiction Screening Test (SAST), 111 they were less open to experiences and more neurotic (as assessed by the Big Five Index).…”
Section: Personality Traitsmentioning
confidence: 99%
“…Two key cognitive and behavioural components that relate to CSBD and other addictive behaviours are thought suppression (e.g. Erskine et al, 2012;Klein, 2007;Riley, 2014) and impulsivity (Hartmann, Czaja, Rief, & Hilbert, 2010;Hu, Zhen, Yu, Zhang, & Zhang, 2017;Rømer Thomsen et al, 2018;Wetterneck, Burgess, Short, Smith, & Cervantes, 2012).…”
Section: Desire Thinkingmentioning
confidence: 99%
“…There is no consensus on the most optimal measure to model impulsivity. However, the UPPS-P model most effectively and comprehensively captures the multifaceted nature of impulsivity by dividing this complex construct into five related empirical dimensions [50]. Furthermore, given that prior measures of impulsivity were used to create the UPPS-P model, it appears to be a framework that is particularly well suited for studies of the impulsivity construct [48,51].…”
Section: Impulsivitymentioning
confidence: 99%